Factors associated with dropout at 2 years post-initiation of treatment in the first episode of schizophrenia - Jebril M. Benelmokhtar; Bonginkosi Chiliza; Lebogang Phahladira; Robin Emsley; Laila Asmal (South African Journal of Psychiatry, 2021)
Background:Prevention of new episodes during the first 2 years after a first episode of schizophrenia (FES) may delay treatment refractoriness and brain morphological changes over time. However, adherence to treatment is characteristically poor in these patients. Aim: The aim of this study was to examine clinical and sociodemographic factors associated with patient dropout in patients with FES.